LEGAL ASPECTS OF INTERNATIONAL COOPERATION IN THE FIELD OF PEACEFUL USES OF NUCLEAR ENERGY: TECHNOLOGY TRANSFER, TRAINING AND EXCHANGE OF EXPERIENCE. - Sayidkomil Bekpulat ugli Ibodullaev (Scholar Express Journals, 2024)
This paper examines the legal frameworks enabling international cooperation on the peaceful uses of nuclear energy, focusing on technology transfer, training programs, and exchange of expertise. Key issues analyzed include relevant international treaties and national policies regulating nuclear technology sharing, human resource development, and collaborative projects. Challenges such as nuclear proliferation risks, trade barriers, and uneven global participation are discussed. Recommendations center on strengthening international norms and institutions to promote capacity building and knowledge transfer while balancing nonproliferation objectives
Keywords: Nuclear Energy; International Cooperation; Technology Transfer; Training